Autoinfarction of Giant Parathyroid Adenoma after Preoperative Withdrawal of Anticoagulants - Raoul Verzijl; Pim J. Bongers; Geetha Mukerji; Ozgur Mete; Karen M. Devon; Jesse D. Pasternak (Case Reports in Surgery)
A 71-year-old man with known history of atrial fibrillation (treated with routine rivaroxaban therapy) was found to have incidental biochemical elevated calcium and parathyroid hormone (PTH) levels. His physical examination demonstrated the presence of a palpable right neck mass. Subsequent imaging studies revealed a large parathyroid mass as well as multiple bone lesions, raising the suspicion of parathyroid carcinoma. The anticoagulant therapy was stopped 5 days prior to his elective surgery. The night before his elective surgery, he presented to the emergency room with profound hypocalcemia. The surgery was postponed and rescheduled after calcium correction. Intraoperative findings and detailed histopathological examination revealed an infarcted 4.0 cm parathyroid adenoma with cystic change. His bony changes were related to brown tumors associated with long-standing hyperparathyroidism. Autoinfarction of a large parathyroid adenoma causing severe hypocalcemia is a rare phenomenon and may be considered in patients with large parathyroid adenomas after withdrawal of anticoagulants.